Cocaine-Induced Cardiac Alterations: Histological and Immunohistochemical Post-Mortem Analysis - Valeria Palumbo; Michele Treglia; Manuel Scimeca; Francesca Servadei; Erica Giacobbi; Rita Bonfiglio; Margherita Pallocci; Pierluigi Passalacqua; Fabio Del Duca; Roberta Tittarelli; Luca Coppeta; Stefania Schiaroli; et al. (Diagnostics)
Background: Cocaine abuse represents a serious health issue. The cardiovascular system is one of the main sites on which cocaine elicits its toxicity, as indicated by deadly events mainly related to myocardial infarction. The main aim of this study was to characterize the histological and immunohistochemical alterations related to cocaine abuse in cardiac tissue. Methods: Cardiac tissue samples derived from cocaine-related (n = 30) and not-cocaine-related deaths (n = 30). Histomorphology evaluations and immunohistochemistry for inflammatory biomarkers (CD45 and CD3) have been performed on formalin-fixed, paraffin-embedded (FFPE) cardiac tissue samples. Results: A higher frequency of cardiac alterations, such as wavy fibers, interstitial edema, fibrosis and hemorrhagic extravasation, were found in the group of cocaine users compared to the control group. Moreover, immunohistochemical analysis showed higher levels of inflammatory cells infiltrate within the cocaine-related deaths group. Conclusions: These data could shed new light on the complex relationship between cocaine use and cardiac alterations. Specifically, our data support the evidence that cocaine abuse is related to cardiac inflammation. Therefore, the generation of an inflammatory state could promote functional and structural cardiac alterations and lead ultimately to myocardial infarction. This would explain the high frequency of acute myocardial infarction in cocaine users.